Preference criteria for online shopping among university students - Ahamat, Amiruddin; Shahkat Ali, Muhamad Sham (Inderscience Enterprises Ltd, 2019)
We are now living in the era of technology and the use of e-commerce is increasing every day, which has become increasingly more important as most activities can be done by using e-commerce, thus aiding the business industry. The younger generation especially students nowadays spend hours on the internet. The aim of this research was to identify the preference criteria among Malaysian university students. It also identified the relationship between the independent variables (situational factors, trust and consumer trait) which were the preference criteria and the dependent variable (online shopping) among Malaysian university students. In this research, the preference criteria that drove them to shop online was analysed using the survey method distributed to 200 university students. The results of this research showed a strong correlation between online shopping and situational factors, a weak correlation between online shopping and trust, and a strong correlation between online shopping and consumer trait.